National Strategy of The United States on Defense Diplomacy for Confidence-Building Measure Efforts with the Philippines in the Era of President Donald Trump - Aldelita Putri Balqis Romulia; Anak Agung Banyu Perwita; Rizerius Eko Hadisancoko; Fauzia Gustarina Cempaka Timur (Jurnal Kewarganegaraan, 2023)
Abstract The bilateral relations between the United States and the Philippines are strong and both nations are in an alliance that foundation on shared values, interests, and history. Both nations have been tied in defense agreements for decades to share collective security. However, in 2016 the last period of President Obama's administration and Presidential transition in the Philippines that elected President Rodrigo Duterte created distance relations in the defense field because of the different perspectives on drug issues and undermining each other's trust. This research will focus on the efforts of the next US administration under President Donald Trump on defense diplomacy for confidence-building measures with the Philippines. The analysis will be based on the confidence-building measures framework that refers to measures to address or resolve uncertainty between states and to prevent wanted or unwanted escalations of hostilities. President Donald Trump has changed the complexity of bilateral relations between the US and the Philippines. American First foreign policy became an instrument of President Trump to reaffirm defense diplomacy with President Duterte, the same perspective on drug issues between the two leaders has rebuilt their mutual trust and determined to continue promoting the mutual goals of peace, and stability in the Asia-Pacific region and around the world. Keywords: Defense Diplomacy, Confidence-Building Measures, Donald Trump, and The Philippines. Abstrak Hubungan bilateral antara Amerika Serikat dan Filipina kuat dan kedua negara berada dalam aliansi yang didasarkan pada nilai, kepentingan, dan sejarah bersama. Kedua negara telah terikat dalam perjanjian pertahanan selama beberapa dekade untuk berbagi keamanan kolektif. Namun, pada tahun 2016 periode terakhir pemerintahan Presiden Obama dan transisi Presiden di Filipina yang memilih Presiden Rodrigo Duterte menciptakan hubungan jarak jauh di bidang pertahanan karena perbedaan cara pandang terhadap masalah narkoba dan saling melemahkan kepercayaan satu sama lain. Penelitian ini akan fokus pada upaya pemerintahan AS selanjutnya di bawah Presiden Donald Trump dalam diplomasi pertahanan untuk membangun kepercayaan dengan Filipina. Analisis ini akan didasarkan pada kerangka “confidence-building measures” yang mengacu pada langkah-langkah untuk mengatasi atau menyelesaikan ketidakpastian antar negara dan untuk mencegah peningkatan permusuhan yang diinginkan atau tidak diinginkan. Presiden Donald Trump telah mengubah kompleksitas hubungan bilateral antara AS dan Filipina. Kebijakan luar negeri “American First” menjadi instrumen Presiden Trump untuk menegaskan kembali diplomasi pertahanan dengan Presiden Duterte, perspektif yang sama mengenai masalah narkoba antara kedua pemimpin telah membangun kembali rasa saling percaya dan bertekad untuk terus mendorong tujuan bersama yaitu perdamaian, dan stabilitas di kawasan Asia-Pasifik dan seluruh dunia. Kata Kunci: Diplomasi Pertahanan, Confidence-Building Measures, Donald Trump, dan Filipina